Stress, Personality, Attachment, and Coping Strategies During the COVID-19 Pandemic: The STERACOVID Prospective Cohort Study Protocol - Edjolo, Arlette; Dorey, Jean-Michel; Herrmann, Mathieu; Perrot, Catherine; Lebrun-Givois, Cécile; Buisson, Aurélie; El Haouari, Hanane; Laurent, Bernard; Pongan, Elodie; Rouch, Isabelle (Frontiers in Psychiatry, 2022)
Background: Due to the lockdown linked to the Covid-19 pandemic, the French National Authority for Health has recommended reinforced follow-up of psychiatric patients, with particular attention to people over 65 years. Cross-sectional studies reported an increased risk of anxiety, depression, and suicide during this period. Older people with psychiatric disorders are at higher risk of developing severe Covid-19 and worsening their psychiatric symptoms. Objective: The main objective is to evaluate the link between coping strategies and the onset of post-traumatic stress disorder (PTSD) after lockdown. The secondary objective is to assess the psychological factors influencing lockdown experiences such as personality, attachment type, or coping strategies. Method/Design: this is a multicenter cohort study including 117 patients followed up by phone in two French geriatric psychiatry units. Sociodemographic variables, psychiatric diagnoses, lockdown conditions, coping strategies, anxiety, and depressive symptoms reported during the first lockdown will be collected retrospectively from the medical file. A first prospective assessment including personality traits, attachment type, and traumatic life events will be conducted at 12 months (T1). Follow-up visits assessing anxious-depressive symptoms and PTSD will be made 18 (T2) and 24 months (T3) after the first lockdown. The primary outcome measure is PTSD symptoms. Secondary outcomes measures are coping strategies, generalized anxiety, anxiety about the Covid-19 pandemic, and quality of life. Discussion: This study aims to determine if the type of coping strategies usually employed have an impact on the onset of PTSD after a lockdown period. It will also determine if these coping strategies are influenced by other factors such as sociodemographic variables, lockdown conditions, particular personality traits, attachment type, and traumatic life events. This study could help identify factors associated with a poorer experience of lockdowns and pandemic crisis in elderly patients followed in a psychiatric center, and guide support in future similar situations.